PKM KEWIRAUSAHAAN BERBASIS TEKNOLOGI INFORMASI DI LINGKUNGAN RW.011 CIPINANG MELAYU - Sri Mardiyati; Ida Fitriani; Yossi Indrawati Syuhardi; Pujiastuti Pujiastuti; Arief Nugroho Wibowo; Dona Fitria; Burhanudin Burhanudin (Abdi Jurnal Publikasi, 2023)
The use of information technology for entrepreneurship in RW.011 Cipinang Melayu has the potential to improve the economy and improve the welfare of the surrounding community. That is, technological advances have opened up new opportunities for entrepreneurs to create innovative businesses. By implementing information technology-based entrepreneurship, the economic gap between urban and rural areas can be reduced and people can more easily access resources. However, there are obstacles such as a lack of knowledge and skills in information technology, which can be overcome through training and increased digital literacy. By answering these challenges, information technology-based entrepreneurship can provide great benefits to the people of RW.011 Cipinang Melayu.